2021
DOI: 10.3390/plants10102198
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Combined Metabolomics-Flavoromics during the Ripening of Mango (Mangifera indica L.) cv. ‘Nam Dok Mai Si Thong’ and ‘Nam Dok Mai No. 4’

Abstract: A metabolomics-flavoromics approach was conducted to assess the micromolecules of ‘Nam Dok Mai Si Thong’ and ‘Nam Dok Mai No. 4’ mango cultivars from two seasons. During ripening, FAMEs, FFAs, fatty alcohols, sterols, and organic acids were dominant at 0–2 days, whereas amino acids, sugars, and volatile organic compounds, including esters, alcohols, ketones, aldehydes, and terpenes, were at higher levels at 4–8 days. Nine metabolites (palmitic/linoleic/linolenic/citric/malic acids, β-sitosterol, sucrose, glyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The reduction in flavonoid content seen during the earlier stages of the ripening process in the current study might be due to the low expression of synthase, as recorded elsewhere in Ataulfo mango [38]. The apparent increase in flavonoids in maximally ripened fruits in the current study may be explained by increased disease/damage in these fruits occurring later in the ripening process [3,4], which could be expected to cause an accumulation of flavonoids, as well as anthocyanin, as a response to these stresses [39][40][41].…”
Section: Fruit Ripening Characteristicssupporting
confidence: 57%
“…The reduction in flavonoid content seen during the earlier stages of the ripening process in the current study might be due to the low expression of synthase, as recorded elsewhere in Ataulfo mango [38]. The apparent increase in flavonoids in maximally ripened fruits in the current study may be explained by increased disease/damage in these fruits occurring later in the ripening process [3,4], which could be expected to cause an accumulation of flavonoids, as well as anthocyanin, as a response to these stresses [39][40][41].…”
Section: Fruit Ripening Characteristicssupporting
confidence: 57%
“…Aung et al evaluated the micromolecules of two mango varieties in two seasons by metabolomics and flavor omics. The results show that there are different biomarkers at different ripening stages, and the biomarker compounds at different changing stages are also identified, providing new insights into the different ripening stages of the two mango varieties in two seasons and the subsequent preservation measures (Lin Aung et al, 2021). Flavoromics has high accuracy, wide application range, high efficiency, and rapid analysis, and it can automatically establish models, creating full automation of data processing very convenient.…”
Section: Application Of Other Omics In the Storage And Transportation...mentioning
confidence: 99%
“…121 Their study identified potential biomarkers such as citric/malic acid, sucrose, amino acids, and palmitic/linoleic/linolenic acids, potentially revealing relationships between ripening-related flavors and particular groups of metabolites during ripening stage. 27,121 The ratio of palmitic-palmitoleic acid in ripening mango pulp determines the association between aroma intensity and flavor. 122 Overall, these studies reveal that in addition to volatiles, the proportion of sugars, amino acids, organic acids, and several together metabolites is also involved in the perception of flavor and aroma of mango fruits.…”
Section: ■ Metabolomicsmentioning
confidence: 99%
“…‘Nam Dok Mai Si Thong’ and ‘Nam Dok Mai No. 4’ . Their study identified potential biomarkers such as citric/malic acid, sucrose, amino acids, and palmitic/linoleic/linolenic acids, potentially revealing relationships between ripening-related flavors and particular groups of metabolites during ripening stage. , The ratio of palmitic-palmitoleic acid in ripening mango pulp determines the association between aroma intensity and flavor .…”
Section: Metabolomicsmentioning
confidence: 99%